Lignin Peroxidase Oxidation of Aromatic Compounds in Systems Containing Organic Solvents - Vazquez-Duhalt, Rafael (1994)
Lignin peroxidase from Phanerochaete chrysosporium was used to study the oxidation of aromatic compounds, including polycyclic aromatic hydrocarbons and heterocyclic compounds, that are models of moieties of asphaltene molecules. The oxidations were done in systems containing water-miscible organic solvents, including methanol, isopropanol, N, N-dimethylformamide, acetonitrile, and tetrahydrofuran. Of the 20 aromatic compounds tested, 9 were oxidized by lignin peroxidase in the presence of hydrogen peroxide. These included anthracene, 1-, 2-, and 9-methylanthracenes, acenaphthene, fluoranthene, pyrene, carbazole, and dibenzothiophene. Of the compounds studied, lignin peroxidase was able to oxidize those with ionization potentials of <8 eV (measured by electron impact). The reaction products contain hydroxyl and keto groups. In one case, carbon-carbon bond cleavage, yielding anthraquinone from 9-methylanthracene, was detected. Kinetic constants and stability characteristics of lignin peroxidase were determined by using pyrene as the substrate in systems containing different amounts of organic solvent. Benzyl alkylation of lignin peroxidase improved its activity in a system containing water-miscible organic solvent but did not increase its resistance to inactivation at high solvent concentrations.